In vitro activity of imipenem/relebactam against piperacillin/tazobactam-resistant and meropenem-resistant non-Morganellaceae Enterobacterales and Pseudomonas aeruginosa collected from patients with bloodstream, intra-abdominal and urinary tract infections in Western Europe: SMART 2018–2020. Issue 2 (10th February 2023) - Karlowsky, James A.; Lob, Sibylle H.; Siddiqui, Fakhar; Akrich, Brune; DeRyke, C. Andrew; Young, Katherine; Motyl, Mary R.; Hawser, Stephen P.; Sahm, Daniel F.
Abstract : Introduction. Piperacillin/tazobactam and carbapenems are important agents for the treatment of serious Gram-negative infections in hospitalized patients. Resistance to both agents is a significant concern in clinical isolates of Enterobacterales and Pseudomonas aeruginosa ; new agents with improved activity are needed. Gap Statement. Publication of current, region-specific data describing the in vitro activity of newer agents such as imipenem/relebactam (IMR) against piperacillin/tazobactam-resistant and carbapenem-resistant Enterobacterales and P. aeruginosa are needed to support their clinical use. Aim. To describe the in vitro activity of IMR against non- Morganellaceae Enterobacterales (NME) and P. aeruginosa isolated from bloodstream, intra-abdominal and urinary tract infection samples by hospital laboratories in Western Europe with a focus on the activity of IMR against piperacillin/tazobactam-resistant and meropenem-resistant isolates. Methodology. From 2018 to 2020, 29 hospital laboratories in six countries in Western Europe participated in the SMART global surveillance programme and contributed 9487 NME and 1004 P . aeruginosa isolates. MICs were determined by CLSI broth microdilution testing and interpreted by EUCAST (2021) breakpoints. β-Lactamase genes were identified in selected isolate subsets (2018–2020) and oprD sequenced in molecularly characterized P. aeruginosa (2020). Results. IMR (99.4 % susceptible), amikacin (98.0 %), meropenem (97.7 %) and imipenem (97.6 %) were the most active agents against NME; 83.1 % of NME were piperacillin/tazobactam-susceptible. Relebactam increased imipenem susceptibility of NME from Italy by 8.3 %, from Portugal by 2.9 %, and from France, Germany, Spain and the UK by <1 %. In total, 96.4 % of piperacillin/tazobactam-resistant ( n =1601) and 73.7 % of meropenem-resistant ( n =152) NME were IMR-susceptible. Also, 0.4 % of NME were MBL-positive, 0.9 % OXA-48-like-positive (MBL-negative) and 1.5 % KPC-positive (MBL-negative). Amikacin (95.4 % susceptible) and IMR (94.1 %) were the most active agents against P. aeruginosa ; 81.7 % of isolates were imipenem-susceptible and 79.6 % were piperacillin/tazobactam-susceptible. Relebactam increased susceptibility to imipenem by 12.5 % overall (range by country, 4.3–17.5 %); and by 30.7 % in piperacillin/tazobactam-resistant and 24.3 % in meropenem-resistant P. aeruginosa . In total, 1.6 % of P. aeruginosa isolates were MBL-positive. Seven of eight molecularly characterized IMR-resistant P. aeruginosa isolates from 2020 were oprD -deficient. Conclusion. IMR may be a potential treatment option for bloodstream, intra-abdominal and urinary tract infections caused by NME and P. aeruginosa in Western Europe, including infections caused by piperacillin/tazobactam-resistant and meropenem-resistant isolates.